2017
DOI: 10.1080/09168451.2017.1313694
|View full text |Cite|
|
Sign up to set email alerts
|

Auxin signaling through SCFTIR1/AFBs mediates feedback regulation of IAA biosynthesis

Abstract: We previously reported that exogenous application of auxin to Arabidopsis seedlings resulted in downregulation of indole-3-acetic acid (IAA) biosynthesis genes in a feedback manner. In this study, we investigated the involvement of the SCF-mediated signaling pathway in feedback regulation of the indole-3-pyruvic acid-mediated auxin biosynthesis pathway in Arabidopsis. Application of PEO-IAA, an inhibitor of the IAA signal transduction pathway, to wild-type seedlings resulted in increased endogenous IAA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…2D), provides a reasonable explanation for this result, as we have previously shown that elevated levels of endogenous auxin promotes growth of PtoDC3000 (32). Further, our observation that tir1 afb1 afb4 afb5 plants exhibit elevated IAA levels is consistent with recent findings that homeostasis of endogenous IAA is maintained by feedback regulation through the canonical auxin signaling pathway (27). Consistent with the role for IAA in suppressing SA signaling, we demonstrated that the tir1 afb1 afb4 afb5 mutant plants exhibited significantly reduced expression of PR-1 and reduced SA levels compared to WT plants at 24h post inoculation ( Fig.…”
Section: Host Auxin Signaling Is Required For Normal Susceptibility Tsupporting
confidence: 92%
See 1 more Smart Citation
“…2D), provides a reasonable explanation for this result, as we have previously shown that elevated levels of endogenous auxin promotes growth of PtoDC3000 (32). Further, our observation that tir1 afb1 afb4 afb5 plants exhibit elevated IAA levels is consistent with recent findings that homeostasis of endogenous IAA is maintained by feedback regulation through the canonical auxin signaling pathway (27). Consistent with the role for IAA in suppressing SA signaling, we demonstrated that the tir1 afb1 afb4 afb5 mutant plants exhibited significantly reduced expression of PR-1 and reduced SA levels compared to WT plants at 24h post inoculation ( Fig.…”
Section: Host Auxin Signaling Is Required For Normal Susceptibility Tsupporting
confidence: 92%
“…It is not immediately obvious why the tir1 afb1 afb4 afb5 mutant, which has decreased auxin-responsive gene expression, exhibits enhanced susceptibility to PtoDC3000. We hypothesized that the tir1 afb1 afb4 afb5 plants might accumulate elevated levels of IAA, due to disruption of the feedback mechanism that normally maintains IAA homeostasis in WT plants (27) and that this elevated IAA promotes susceptibility. To investigate whether the enhanced pathogen growth in tir1 afb1 afb4 afb5 plants is correlated with elevated IAA in host tissue, we quantified free IAA levels in WT Col-0 and tir1 afb1 afb4 afb5, in both PtoDC3000-infected and mock-treated plants at 24h post inoculation.…”
Section: The Tir1 Afb1 Afb4 Afb5 Mutant Accumulates Elevated Levels Omentioning
confidence: 99%
“…We further selected several known auxin-responsive genes in angiosperms and determined the expression of their homologues in our RNA-seq dataset. It is known that class II homeodomain-leucine zipper ( C2HDZ ), WIP , and YUCCA ( YUC ) genes are regulated by auxin in A. thaliana (Crawford et al, 2015; Sawa et al, 2002; Takato et al, 2017). We identified C2HDZ and WIP to be commonly activated by auxin in all land plants in our RNA-seq (note that no WIP gene was identified in the A. agrestis assembly).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, only limited information is available for the molecular modifications of YUC genes or proteins to regulate active auxin levels. It was found that active auxin itself could regulate YUC gene expressions via a negative feedback manner in Arabidopsis [159,160]. Under excess auxin conditions, the four essential YUCs (YUC1, 2, 4, and 6) were transcriptionally downregulated and upregulated under auxin-deficient conditions [159].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%